Chapter The influence of natural conditions on the service of rear formations of the Polish Army during the Polish-Soviet war in 1919–1921 - Roguski, Rafał (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
In the following article, the author will present the impact of terrain on the service and condition of soldiers stationed in the front, in the so-called stage area. The author will also present the problem of infectious diseases troubling soldiers serving in the back of the front line. The work was based primarily on the archival materials from the Central Military Archives in Warsaw, created by the Command of the Stage Districts and the Command of the Stage Poviats from the period of wars for the borders of Poland 1919–1921.